2019
DOI: 10.1038/s41598-019-38852-9
|View full text |Cite
|
Sign up to set email alerts
|

A critical evaluation of TRPA1-mediated locomotor behavior in zebrafish as a screening tool for novel anti-nociceptive drug discovery

Abstract: Current medications inadequately treat the symptoms of chronic pain experienced by over 50 million people in the United States, and may come with substantial adverse effects signifying the need to find novel treatments. One novel therapeutic target is the Transient Receptor Potential A1 channel (TRPA1), an ion channel that mediates nociception through calcium influx of sensory neurons. Drug discovery still relies heavily on animal models, including zebrafish, a species in which TRPA1 activation produces hyperl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 41 publications
(51 reference statements)
3
14
0
Order By: Relevance
“…Furthermore, annelid worms are a favourite food item of C. batrachus (Das, 1928) and were found by a survey responder to be in the stomachs of many C. batrachus that were on land and surrounded by annelids. Quinine is a bitter compound that elicits negative taste responses in fish when mixed with food (Lamb & Finger, 1995), and AITC in solution targets TRPA1 nociceptors on solitary chemosensory cells in fish, which are found on the bodies of C. batrachus (Curtright et al, 2015;Hinman et al, 2006;Ko et al, 2019;Kotrschal, 1995), but C. batrachus showed no orientation response to either substance on the substrate. Alternatively, quinine and AITC are barely soluble and insoluble in water, respectively.…”
Section: Survey and Youtube Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, annelid worms are a favourite food item of C. batrachus (Das, 1928) and were found by a survey responder to be in the stomachs of many C. batrachus that were on land and surrounded by annelids. Quinine is a bitter compound that elicits negative taste responses in fish when mixed with food (Lamb & Finger, 1995), and AITC in solution targets TRPA1 nociceptors on solitary chemosensory cells in fish, which are found on the bodies of C. batrachus (Curtright et al, 2015;Hinman et al, 2006;Ko et al, 2019;Kotrschal, 1995), but C. batrachus showed no orientation response to either substance on the substrate. Alternatively, quinine and AITC are barely soluble and insoluble in water, respectively.…”
Section: Survey and Youtube Resultsmentioning
confidence: 99%
“…Quinine is a bitter compound that elicits negative taste responses in fish when mixed with food (Lamb & Finger, 1995), and AITC in solution targets TRPA1 nociceptors on solitary chemosensory cells in fish, which are found on the bodies of C. batrachus (Curtright et al ., 2015; Hinman et al ., 2006; Ko et al ., 2019; Kotrschal, 1995), but C. batrachus showed no orientation response to either substance on the substrate. Therefore, C. batrachus may not use these compounds for terrestrial orientation.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It's unlikely that the concentration of HC-030031 in these experiments was too low to have any significant effect upon basal CPMC activity. Whilst HC-030031 is a relatively weak antagonist of murine TRPA1 channels (pA 2 ∼ 5.5; Ko et al, 2019) the antagonist was tested at an upper concentration shown to be specific for blocking TRPA1 (Capasso et al, 2012) and to cause almost complete inhibition of TRPA1 mediated Ca 2+ currents in HEK cells expressing TRPA1 (McNamara et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Although previous studies had identified optovin analogues 37 , it was unclear whether TRPA1-mediated nonvisual photosensation also occurred with other, more structurally diverse compounds. Through this study, we have demonstrated that there are multiple novel compounds with structural and photochemical properties that differ greatly from those of optovin but are similarly able to induce motor activity in response to light.…”
Section: Light Responsive Compounds Demonstrate Structural Diversitymentioning
confidence: 99%